Public Value Implementasi Kebijakan Permendesa No 7 Tahun 2023 Prioritas Penggunaan Dana Desa di Nagari Taeh Baruah, Kabupaten Lima Puluh Kota - Adita, Vinnanda; Mubarak, Adil (Al-DYAS, 2025)
This study is grounded in the importance of ensuring that the implementation of the Village Fund policy truly creates public value through tangible benefits, transparency, and community participation in nagari development. The research aims to analyze the implementation of Ministerial Regulation of the Ministry of Villages (Permendesa) No. 7 of 2023 on the priority use of Village Funds in Nagari Taeh Baruah and to assess the extent to which the policy generates public value for the community. A descriptive qualitative method was used, with data collected through interviews and documentation. The study focused on four policy priorities: extreme poverty alleviation, food security strengthening, stunting prevention, and the development of Village-Owned Enterprises (BUMNag). The findings indicate that the Village Fund has delivered tangible benefits through the construction of agricultural infrastructure such as roads and irrigation systems, stunting prevention programs, direct cash assistance for low-income families, and community economic empowerment through BUMNag. Policy implementation has been participatory, facilitated through rembuk jorong forums and musyawarah nagari, accompanied by transparent financial reporting. However, several challenges remain, including unequal distribution of aid, inconsistency in health programs, delays in fund disbursement, and limited capacity among local officials. The study concludes that the implementation of the Village Fund policy in Nagari Taeh Baruah has contributed to public value creation by improving welfare, fostering citizen participation, and promoting government transparency, although its effectiveness must be further enhanced to reach all community segments more equitably and sustainably.